Safety of Therapeutic Apheresis in Children and Adolescents - Taylan, Christina; Schaaf, Anne; Dorn, Corina; Schmitt, Claus Peter; Loos, Sebastian; Kanzelmeyer, Nele; Pape, Lars; Müller, Dominik; Weber, Lutz T.; Thumfart, Julia (Frontiers in Pediatrics, 2022)
Background Therapeutic apheresis (TA) is based on the principles of either removing dissolved pathogenic substances (e.g., antibodies) from the blood plasma or replacing plasma factors. It expands the therapeutic scope for a variety of diseases. Safety analysis in the pediatric field are scant. The aim of this analysis was to analyze specific complications of TA modalities – plasma exchange (PE) and immunoadsorption (IA) – in children and adolescents. Methods Children and adolescents (n = 298) who had received TA from 2008 to 2018 in five pediatric nephrology centers were analyzed retrospectively. In total, 4.004 treatments (2.287 PE and 1.717 IA) were evaluated. Results Indications for TA were mainly nephrological and neurological diseases. The three main indications were antibody-mediated graft rejection (13.4%), hemolytic uremic syndrome mainly with neurological involvement (12.8%), and AB0-incompatible transplantation (11.7%). Complications developed in 440 of the 4004 sessions (11%), of which one third were non-specific (nausea, headache). IA was better tolerated than PE. Complications were reported in 9.5% (n = 163) of the IA versus 12.1% (277) of the PE sessions (p < 0.001). When considering different types of complications, significantly more non-specific/non-allergic events (p = 0.02) and allergic reactions occurred in PE sessions (p < 0.001). More complications occurred with PE, when using fresh frozen plasma (16.2%; n = 145) in comparison to human albumin (14.5%; n = 115) (p < 0.001). Conclusions Therapeutic apheresis in childhood and adolescence is a safe treatment procedure. IA showed a lower complication rate than PE. Therefore, IA may be preferably provided if the underlying disease pathomechanisms do not require PE.